Ecuadorian Holstein-Friesian cattle paternal lineages: Demographic structure, inbreeding evolution, and genetic diversity. - Luis F Cartuche-Macas; Miguel A Gutierrez-Reinoso; Edilberto Chacón; Carlos O Larrea-Izurieta; Joar M García-Flores; Manuel Garcia-Herreros (PLoS ONE)
Holstein-Friesian cattle are the most important dairy breed worldwide. The main objective was to carry out a detailed pedigree evaluation of the Ecuadorian Holstein-Friesian cattle to investigate the demographic structure, inbreeding evolution, and genetic diversity of the official paternal lineages to determine the potential GD loss after the inclusion of modern Assisted Reproductive Technologies (ARTs). Official pedigree information from 28,893 Holstein-Friesian sires born between 1950 and 2021 and enrolled with the Ecuadorian Holstein-Friesian Association (AHFE, Ecuador) were recorded and evaluated from USA and Canada genetic official databases. After multiple-trait across-country genetic analyses the total population was divided into four subpopulations; i) 1950-1969: natural mating (NM) period; ii) 1970-1989: NM +  artificial insemination (AI) period; iii) 1990-2009: AI +  embryo transfer (ET) period; and iv) 2010-2021: AI +  ET +  genomic selection (GS) period. Demographic parameters [number of males, pedigree integrity (PI), and generation interval (GI)] were analysed. PI was analysed using known ancestors up to 4 generations considering the number of complete (GCom), maximum (GMax) and equivalent (GEqu) generations. Moreover, Inbreeding parameters [inbreeding coefficient (F), average relatedness (AR), coancestry (C), effective size (Ne), genetic conservation index (GCI)] and parameters related to the gene origin probability (number of founders (f), effective number of founders (fe), genetic conservation index (GCI), among others] were also analysed, together with the fe/f ratio, fge/fe ratio, genetic contributions, and genetic diversity loss (GD-loss) derived parameters. The results indicated that nearly all imported sires used in Ecuador born in the beginning of 1990s could be traced to just three countries, who together account for > 90% of paternal lineages. This fact indicates that GD has undergone a dramatic decrease during the past 30 years. The PCI for the three last periods were > 55%, and the trend was enhanced in the fourth chronological period till > 92%. The estimated proportion of random genetic drift in GD loss increased over time as well as the Ne that decreased by the time. In conclusion, the occurrence of AI +  ET +  GS period led to the major GD loss. Therefore, due to the extremely limited number of paternal lineages the strategy for recovering the minimal GD on the current and future Ecuadorian Holstein-Friesian cattle should reduce the inbreeding values by increasing the Ne using alternately the foreign genetic material and the national breeding stock.